Interior and Exterior of the Chapel at Great Ilford, Essex - Schnebbelie, Robert Blemmell; Wise, William (Tufts Archival Research Center, 2008)
Formerly belonging to the House of Male Lepers founded by Edeliza Abbess of Barking in the reign of King Stephen. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.